Implementasi Kebijakan Pembangunan Daerah melalui Pendekatan Bottom-Up - Muminah, Sulton; Suprajogo, Tjahjo (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Regional development policies play a crucial role in shaping the growth and welfare of local communities. However, the effectiveness of these policies often depends on how well they are implemented at the regional level. Traditional top-down approaches may overlook local conditions and actors, leading to less effective outcomes. This study aims to explore the implementation of regional development policies in Indonesia through a bottom-up approach, which highlights the significance of local actors such as bureaucrats and community members in influencing policy success. Understanding the dynamics of local participation and contextualization is essential for promoting more inclusive and sustainable development. This research employs a qualitative approach with a descriptive method. The object of the study is regional development policies in Indonesia. Data sources include laws and relevant regulations related to regional development. Data collection was conducted through documentation and literature review methods. The collected data were then analyzed using content analysis techniques to identify meanings, patterns, and trends in policy implementation from a bottom-up perspective. Findings indicate that participatory and context-sensitive policy implementation tends to better address local needs, but challenges remain, including limited human resource capacity, budget constraints, dominance of top-down approaches, and weak public oversight. Successful implementation requires synergy among implementers’ flexibility, political support, and active community participation.